Strategic Alignment of Information Technology Initiatives in a Scaled Agile Environment (The Journal of Modern Project Management, 2022)
Scaled Agile introduces challenges that confront organisations. One of these challenges is how initiatives are aligned with the organisational strategies in frameworks such as SAFe. Nineten interviews were conducted within a case that has implemented a scaled Agile framework. The purpose was to determine how this framework was implemented and to assess how information technology (IT) initiatives are aligned with the corporate strategies. The results indicate that IT initiatives are aligned with the strategies but that two approaches are used. Future research will focus on benefits realisation within a scaled Agile environment.